The Two Winged Truth in The Wild Duck: Plato, Ibsen, and Krleža - Tomljenović, Ana (Poznańskie Studia Slawistyczne, 2021)
Questioning the commonly held assumption in critical reception that Ibsenʼs symbol of the wild duck was influenced by Darwinʼs theory, I want to argue that the wild duck flew into Ibsenʼs play all the way from Platoʼs aporetic dialogue The Theaetetus. Following Lacanʼs reading of Plato, I want to examine the connection between the Socratic position towards knowledge – especially the rupture between knowledge and truth – and the treatment of dramatic dialogue in Ibsenʼs The Wild Duck and Krležaʼs The Glembays.